2011
DOI: 10.1073/pnas.1117827108
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous generation of anchorless prions in transgenic mice

Abstract: Some prion protein mutations create anchorless molecules that cause Gerstmann–Sträussler–Scheinker (GSS) disease. To model GSS, we generated transgenic mice expressing cellular prion protein (PrP C ) lacking the glycosylphosphatidyl inositol (GPI) anchor, denoted PrP(ΔGPI). Mice overexpressing PrP(ΔGPI) developed a late-onset, spontaneous neurologic dysfunction characterized by widespread amyloid deposition in the brain and the presence of a short protease-resistant PrP fragment similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 25 publications
(27 reference statements)
3
64
0
Order By: Relevance
“…Upon inoculation with prions, transgenic mice expressing GPI anchorless PrP C supported prion replication and accumulated prion infectivity; however, the disease onset in these mice was substantially delayed or was lacking (29). Mice that overexpressed GPI anchorless PrP C developed neurological dysfunction and generated infectious prions spontaneously in the absence of exposure to prions (30). Previous studies suggested that neurotoxic signaling is dependent on PrP C attachment to the plasma membrane via its GPI anchor (31,32).…”
Section: Prions or Prpmentioning
confidence: 99%
“…Upon inoculation with prions, transgenic mice expressing GPI anchorless PrP C supported prion replication and accumulated prion infectivity; however, the disease onset in these mice was substantially delayed or was lacking (29). Mice that overexpressed GPI anchorless PrP C developed neurological dysfunction and generated infectious prions spontaneously in the absence of exposure to prions (30). Previous studies suggested that neurotoxic signaling is dependent on PrP C attachment to the plasma membrane via its GPI anchor (31,32).…”
Section: Prions or Prpmentioning
confidence: 99%
“…In both models, there are vascular and perivascular deposits of prion protein that are similar in appearance to those in the brains of humans who have inherited prion diseases with PRNP stop-codon mutations. 3,4 This finding suggests that the cerebrovascular phenotype associated with the deposition of prion protein may relate to the loss of the GPI anchor alone, rather than Cterminal truncation of prion protein. One model in transgenic mice showed cardiac defects on testing but no overt clinical signs, 3 whereas a spontaneous and transmissible neurodegenerative disease developed in a second model.…”
Section: Discussionmentioning
confidence: 83%
“…The development of transgenic mice that express prion protein lacking the GPIanchor addition site (known as "anchorless" prion protein) has been of considerable interest, since these mice may propagate infectious prions and abnormal prion protein deposits around blood vessels in the brain and peripheral tissues, but they show highly delayed and variable clinical signs of prion disease. 3,4 In humans, a premature stop-codon mutation also results in abnormal prion protein without a GPI anchor, but clinical reports are very limited. The PRNP Y145X mutation has been described in a single patient with an Alzheimer-type dementia and prion protein amyloid deposition in the cerebral vessels, 5 the Q160X mutation has been described in a small family with dementia, 6 and two C-terminal truncation mutations have been associated with the GSS syndrome in case reports.…”
mentioning
confidence: 99%
“…Although the relative amount of internal PrP Sc fragments was small, these results suggest that PrP species lacking the amino and carboxyl termini represent a molecular fingerprint of anchorless prions. Intriguingly, a 10-kDa internal fragment has been detected in brain tissues of uninfected Tg mice overexpressing anchorless PrP, and in Tg mice co-expressing anchored and anchorless PrP (12). Noteworthy, the aforementioned transgenic mice develop a spontaneous neurologic illness characterized by large PrP amyloid deposits composed by a 10-kDa PK-resistant fragment.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, transgenic mice overexpressing anchorless PrP C develop a spontaneous GSS-like neurologic illness with widespread PrP amyloid deposition in brain tissues, as a result of aggregation and accumulation of an internal PrP fragment (12). Additionally, infection of "anchorless PrP" mice induces the formation of angiocentric amyloid plaques, as opposed to granular PrP Sc deposition observed in wild-type mice (13).…”
mentioning
confidence: 99%